Rapid and sensitive point-of-care detection of Orthopoxviruses by ABICAP immunofiltration. Issue 1 (December 2016) - Stern, Daniel; Olson, Victoria; Smith, Scott; Pietraszczyk, Marko; Miller, Lilija; Miethe, Peter; Dorner, Brigitte; Nitsche, Andreas
Abstract Background The rapid and reliable detection of infectious agents is one of the most challenging tasks in scenarios lacking well-equipped laboratory infrastructure, like diagnostics in rural areas of developing countries. Commercially available point-of-care diagnostic tests for emerging and rare diseases are particularly scarce. Results In this work we present a point-of-care test for the detection ofOrthopoxviruses (OPV). The OPV ABICAP assay detects down to 1 × 104 plaque forming units/mL of OPV particles within 45 min. It can be applied to clinical material like skin crusts and detects all zoonotic OPV infecting humans, includingVaccinia, Cowpox, Monkeypox, and most importantlyVariola virus . Conclusions Given the high sensitivity and the ease of handling, the novel assay could be highly useful for on-site diagnostics of suspectedMonkeypox virus infections in areas lacking proper laboratory infrastructure as well as rapid on-site testing of suspected bioterrorism samples.